(untitled) (Global Journal of Human-Social Science, 2020)
The writer Kate Chopin has written about female sexuality and the restrictions put by marriage as an institution upon the lives of women. Her writings delineate the lives of female characters who are burdened by the relationships they have in society. They are self-assertive and courageous women of the nineteenth century. They are thought to be ahead of their time. They have refused to accept the traditional roles and conventions of the society and have shown the deepest drives of their hearts. Chopin has explored these female souls as a woman writer. Her first attempt is to highlight the sense of female freedom and a true understanding of their nature in her writings.